Optimized Monitoring of Production of Cellulose Nanowhiskers from Opuntia ficus-indica (Nopal Cactus) - Horacio Vieyra; Ulises Figueroa-López; Andrea Guevara-Morales; Berenice Vergara-Porras; Eduardo San Martín-Martínez; Miguel Ángel Aguilar-Mendez (International Journal of Polymer Science)
Preparation of cellulose nanowhiskers (CNWs) has grown significantly because they are useful for a wide range of applications. Additional advantage in their design requires that they meet the following characteristics: nontoxicity, abundance, sustainability, renewability, and low cost. To address these requirements, nanowhiskers were prepared from Opuntia ficus-indica (nopal) cellulose by acid hydrolysis. Monitoring the process of CNWs preparation is necessary to ensure maximum yield and purity of the end product. In this study, the cellulose preparation was monitored by analyzing microscopic morphology by SEM; the purity degree was determined by fluorescence microscopy as a novel and rapid technique, and FTIR spectroscopy was used for confirmation. The additional parameters that monitored the process were the crystallinity index by X-ray diffraction and the size of the particle by dynamic light scattering (DLS). Nopal cellulose was found to be comparable to commercial microcrystalline cellulose. The use of Opuntia ficus-indica is a viable alternative for the production of highly pure CNWs and the strategy to supervise the preparation process was rapid.